Strategies to Overcome Dark Side of Social Media for Organizational Sustainability - Sharma, Jitender (International Journal of Virtual Communities and Social Networking, 2016)
Social media has provided the organizations a massive platform to reach masses and is considered as a highly effective tool for organizations to connect and promote their brands and messages all over the world with huge potential to attract clientele with virtually no or very low investment. It has given organizations a collaborative innovation medium also where shared wisdom can help organizations bringing out innovation in their products and services. Social media reach can result in the spread of positive sentiment about the organization's products or services very fast to large number of people. However social media is a double edge sword. If it has potential to help boosting an organization's business, it can also result in propagating negative image and that too at a very fast speed and to very large user segment. A single negative comment on organization's blog or profile, or a complaint by some customer about organization's product or services on social media may cause a negative and long lasting impact on an organization's and/or a brand's reputation. Hence, social media can make or tarnish an organization's sustainability. Organizations need to be on high alert always. Staying away from social media is not a solution as you are not aloof in the virtual world of social media. Anyone can put anything on the media and information spread is so fast that no one can control the same. Though organizations can be benefitted immensely from use of social media, there are chances that either your internal dissatisfied employees or your customers or even your competitors can spoil your image by putting wrong or unwanted information on social media. Either competitors may hire specialized hackers or individual hackers may hack an organization's media campaign and convey totally opposite message to tarnish the organization's brand image and blackmail. Organizations need to keep a hawk eye on such brand assassins and their social activity and take counter measures very fast so as to defeat such wrongdoers. To succeed in the highly technologically advanced environment, organizations need to make use of social media for their own advantages. They need to conquer dark side of social media by remaining vigilant all the times and adopt such strategies that not only counter malicious intentions of wrong-doers but proved to be effective marketing strategies to effectively promote organizations' interests. This paper is an attempt to understand role of social media in making or tarnishing an organization's image and evolve out strategies to help the organizations conquering dark side of social media.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNDAxOC9panZjc24uMjAxNjAxMDEwNA